Cellular and molecular mechanisms underlying obesity in degenerative spine and joint diseases - Qian Xiang; Zhenquan Wu; Yongzhao Zhao; Shuo Tian; Jialiang Lin; Longjie Wang; Shuai Jiang; Zhuoran Sun; Weishi Li (Bone Research)
Abstract Degenerative spine and joint diseases, including intervertebral disc degeneration (IDD), ossification of the spinal ligaments (OSL), and osteoarthritis (OA), are common musculoskeletal diseases that cause pain or disability to the patients. However, the pathogenesis of these musculoskeletal disorders is complex and has not been elucidated clearly to date. As a matter of fact, the spine and joints are not independent of other organs and tissues. Recently, accumulating evidence demonstrates the association between obesity and degenerative musculoskeletal diseases. Obesity is a common metabolic disease characterized by excessive adipose tissue or abnormal adipose distribution in the body. Excessive mechanical stress is regarded as a critical risk factor for obesity-related pathology. Additionally, obesity-related factors, mainly including lipid metabolism disorder, dysregulated pro-inflammatory adipokines and cytokines, are reported as plausible links between obesity and various human diseases. Importantly, these obesity-related factors are deeply involved in the regulation of cell phenotypes and cell fates, extracellular matrix (ECM) metabolism, and inflammation in the pathophysiological processes of degenerative spine and joint diseases. In this study, we systematically discuss the potential cellular and molecular mechanisms underlying obesity in these degenerative musculoskeletal diseases, and hope to provide novel insights for developing targeted therapeutic strategies.